Solar cells, stacked cells and photovoltaic modules

CN122995270APending Publication Date: 2026-10-27ZHEJIANG AIKO SOLAR ENERGY TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611224364.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本申请的主要目的在于提供一种太阳能电池、叠层电池和光伏组件,以解决现有技术中太阳能电池的光电转换效率较低的问题

Benefits of technology

[0017]应用本申请的技术方案,太阳能电池包括:吸收层、电子传输层、空穴传输层、第一电极和第二电极,其中吸收层包括氧化亚铜和氧化铜;电子传输层位于吸收层的一侧的表面上;空穴传输层位于吸收层背离电子传输层的一侧表面上;第一电极和第二电极分别与电子传输层和空穴传输层接触。本申请通过设置包含氧化亚铜与氧化铜双组分的吸光层,并配合电子传输层与空穴传输层的异质结结构,可以提升太阳能电池的光电转换效率。具体而言,氧化亚铜作为宽带隙材料,提供了良好的晶格基础;而引入的氧化铜作为窄带隙组分,有效弥补了氧化亚铜对长波段太阳光吸收不足的缺陷,从而大幅增强了器件对全光谱太阳光的利用能力,提高了短路电流密度。同时,氧化铜与氧化亚铜之间形成的微观异质结或界面势垒,有利于光生载流子的分离与传输,减少了复合损失。配合两侧的选择性电荷传输层,可以进一步实现电子与空穴的高效定向收集至相应电极,降低串联电阻,最终使得电池在保持低成本优势的同时,实现了更高的开路电压和填充因子,整体光电转换效率得到实质性提升,进而解决了现有技术中太阳能电池的光电转换效率较低的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995270A_ABST
    Figure CN122995270A_ABST
Patent Text Reader

Abstract

The application provides a solar cell, a laminated cell and a photovoltaic module. The solar cell comprises: an absorption layer comprising cuprous oxide and copper oxide; an electron transport layer located on a surface of one side of the absorption layer; a hole transport layer located on a surface of one side of the absorption layer away from the electron transport layer; and a first electrode and a second electrode in contact with the electron transport layer and the hole transport layer respectively. The application solves the problem of low photoelectric conversion efficiency of the solar cell in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solar cell technology, and more specifically, to a solar cell, a tandem cell, and a photovoltaic module. Background Technology

[0002] Solar energy, as a clean, renewable, and green energy source, has attracted much attention for its development and utilization. Among various thin-film solar cell technologies, cuprous oxide (Cu2O) solar cells have become one of the photovoltaic materials with great application potential due to their abundant material reserves, non-toxicity, low cost, and direct bandgap characteristics.

[0003] However, existing technologies still have some limitations in application. First, the wide bandgap of cuprous oxide results in weak absorption of long-wavelength light in the solar spectrum, limiting the improvement of the battery's short-circuit current density. Second, although cuprous oxide has theoretically high conversion efficiency, its short carrier lifetime and high defect state density mean that the photoelectric conversion efficiency of actual devices often falls short of the theoretical limit, remaining far below the level of current mainstream crystalline silicon solar cells. Furthermore, simply optimizing the quality of the cuprous oxide thin film cannot fundamentally solve the problem of insufficient absorption spectral width.

[0004] The information disclosed in the background section is only intended to enhance the understanding of the background art of the art described herein. Therefore, the background art may contain information that does not constitute prior art known to those skilled in the art in this country. Summary of the Invention

[0005] The main objective of this application is to provide a solar cell, a tandem cell, and a photovoltaic module to solve the problem of low photoelectric conversion efficiency in existing solar cells.

[0006] To achieve the above objectives, according to one aspect of this application, a solar cell is provided, comprising: an absorber layer including cuprous oxide and copper oxide; an electron transport layer located on one side surface of the absorber layer; a hole transport layer located on the side surface of the absorber layer opposite to the electron transport layer; a first electrode and a second electrode respectively in contact with the electron transport layer and the hole transport layer.

[0007] Optionally, the cuprous oxide structural layer has a first surface and a second surface disposed opposite to each other, and the copper oxide structural layer is located on at least one of the first surface and the second surface.

[0008] Optionally, a transition layer is provided between the cuprous oxide structural layer and the copper oxide structural layer, wherein the atomic ratio of copper to oxygen in the transition layer is located between the atomic ratio of copper to oxygen in the cuprous oxide structural layer and the atomic ratio of copper to oxygen in the copper oxide structural layer.

[0009] Optionally, the thickness of the copper oxide structural layer ranges from 10 nm to 200 nm.

[0010] Optionally, the cuprous oxide structural layer includes the copper oxide.

[0011] Optionally, the mass percentage of copper oxide in the cuprous oxide structural layer ranges from 0% to 10%.

[0012] Optionally, the copper oxide may be in the form of at least one of the following: nanoparticles, microparticles, flakes, discontinuous films, and continuous films.

[0013] According to another aspect of this application, a method for fabricating a solar cell is provided. The method includes: providing an absorber layer comprising cuprous oxide and copper oxide; forming an electron transport layer on one side surface of the absorber layer; forming a hole transport layer on the side surface of the absorber layer opposite to the electron transport layer; and forming a first electrode and a second electrode in contact with the electron transport layer and the hole transport layer, respectively.

[0014] Optionally, the step of forming the absorber layer includes: providing a substrate; forming a cuprous oxide structural layer on the substrate using a magnetron sputtering process, wherein during the preparation of the absorber layer using the magnetron sputtering process, argon and oxygen are introduced into the surface of the substrate, the target material is copper, and the atomic ratio of argon to oxygen is 5:1 to 10:1; forming a transition layer on the cuprous oxide structural layer using a magnetron sputtering process, wherein during the preparation of the absorber layer using the magnetron sputtering process, the atomic ratio of argon to oxygen is 1:3 to 3:1; forming a copper oxide structural layer on the transition layer using a magnetron sputtering process, wherein during the preparation of the absorber layer using the magnetron sputtering process, the atomic ratio of argon to oxygen is 1:10 to 1:1.

[0015] According to another aspect of this application, a stacked battery is provided, comprising a bottom battery and a top battery, wherein the top battery is the aforementioned solar cell.

[0016] According to another aspect of this application, a photovoltaic module is provided, comprising a plurality of the aforementioned solar cells.

[0017] According to the technical solution of this application, a solar cell includes: an absorber layer, an electron transport layer, a hole transport layer, a first electrode, and a second electrode. The absorber layer comprises cuprous oxide and copper oxide. The electron transport layer is located on one side of the absorber layer's surface. The hole transport layer is located on the side of the absorber layer facing away from the electron transport layer. The first electrode and the second electrode are in contact with the electron transport layer and the hole transport layer, respectively. This application improves the photoelectric conversion efficiency of the solar cell by setting a light-absorbing layer containing both cuprous oxide and copper oxide components, combined with a heterojunction structure of the electron transport layer and the hole transport layer. Specifically, cuprous oxide, as a wide bandgap material, provides a good lattice basis; while the introduced copper oxide, as a narrow bandgap component, effectively compensates for the insufficient absorption of long-wavelength sunlight by cuprous oxide, thereby significantly enhancing the device's ability to utilize the full spectrum of sunlight and increasing the short-circuit current density. Simultaneously, the microscopic heterojunction or interface barrier formed between copper oxide and cuprous oxide facilitates the separation and transport of photogenerated carriers, reducing recombination losses. With the selective charge transport layers on both sides, electrons and holes can be efficiently and directionally collected to the corresponding electrodes, reducing series resistance. Ultimately, while maintaining the low-cost advantage, the battery achieves higher open-circuit voltage and fill factor, resulting in a substantial improvement in overall photoelectric conversion efficiency. This solves the problem of low photoelectric conversion efficiency in existing solar cells. Attached Figure Description

[0018] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:

[0019] Figure 1 A cross-sectional structural schematic diagram of a first type of solar cell according to an embodiment of this application is shown;

[0020] Figure 2 A cross-sectional structural schematic diagram of a second type of solar cell according to an embodiment of this application is shown;

[0021] Figure 3 A cross-sectional structural schematic diagram of a third type of solar cell according to an embodiment of this application is shown;

[0022] Figure 4 A schematic flowchart of a method for fabricating a solar cell according to an embodiment of this application is shown.

[0023] The above figures include the following reference numerals:

[0024] 10. Absorbing layer; 11. Cuprous oxide; 12. Copper oxide; 20. Electron transport layer; 30. Hole transport layer; 40. First electrode; 50. Second electrode. Detailed Implementation

[0025] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0026] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0027] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate for the embodiments of the invention described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.

[0028] It should be understood that when an element (such as a layer, film, region, or substrate) is described as being "on" another element, the element may be directly on the other element, or there may be an intermediate element present. Furthermore, in the specification and claims, when an element is described as being "connected" to another element, the element may be "directly connected" to the other element, or "connected" to the other element via a third element.

[0029] As described in the background section, cuprous oxide in the prior art has a weak absorption capacity for long-wavelength light in the solar spectrum, which limits the improvement of the short-circuit current density of the battery. Due to its short carrier lifetime and high defect state density, the actual photoelectric conversion efficiency of the device is lower than that of the current mainstream crystalline silicon battery. Moreover, simply optimizing the quality of the cuprous oxide thin film is not enough to fundamentally solve the problem of insufficient absorption spectrum. In order to solve the problem of low photoelectric conversion efficiency of solar cells in the prior art, the embodiments of this application provide a solar cell, a tandem cell, and a photovoltaic module.

[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.

[0031] According to one embodiment of this application, a solar cell is provided, such as Figures 1 to 3 As shown, it includes: an absorption layer 10, comprising cuprous oxide and copper oxide; an electron transport layer 20, located on one side of the surface of the absorption layer 10; a hole transport layer 30, located on the side of the absorption layer 10 opposite to the electron transport layer 20; a first electrode 40 and a second electrode 50, respectively in contact with the electron transport layer 20 and the hole transport layer 30.

[0032] This application improves the photoelectric conversion efficiency of solar cells by setting a light-absorbing layer containing both cuprous oxide and copper oxide, combined with a heterojunction structure of an electron transport layer and a hole transport layer. Specifically, cuprous oxide, as a wide bandgap material, provides a good lattice basis; while the introduced copper oxide, as a narrow bandgap component, effectively compensates for the insufficient absorption of long-wavelength sunlight by cuprous oxide, thereby significantly enhancing the device's ability to utilize the full spectrum of sunlight and increasing the short-circuit current density. Simultaneously, the microscopic heterojunction or interface barrier formed between copper oxide and cuprous oxide facilitates the separation and transport of photogenerated carriers, reducing recombination losses. Combined with the selective charge transport layers on both sides, efficient directional collection of electrons and holes to the corresponding electrodes can be further achieved, reducing series resistance. Ultimately, while maintaining the low-cost advantage, the cell achieves a higher open-circuit voltage and fill factor, resulting in a substantial improvement in overall photoelectric conversion efficiency, thus solving the problem of low photoelectric conversion efficiency in existing solar cells.

[0033] In the above embodiments, the absorption layer is the core functional component of the solar cell, enabling the capture and conversion of light energy. In this application, the absorption layer is composed of two components: cuprous oxide and copper oxide. Cuprous oxide serves as the host material, providing the main crystal lattice structure. Copper oxide has a narrower band gap and a higher light absorption coefficient, exhibiting excellent optical performance, particularly in the long-wavelength range (red to near-infrared region). Therefore, the introduction of copper oxide can compensate for the relatively wide band gap of cuprous oxide. By controlling the ratio and distribution morphology of the two components (e.g., they can be uniformly mixed or stacked), the absorption layer can effectively broaden the spectral response range of the device, increase the photon absorption rate, and thus improve the generation efficiency of photogenerated carriers.

[0034] In the above embodiments, the electron transport layer can be located on the side of the absorption layer near the light-receiving surface or on the side of the absorption layer near the back-light-receiving surface. The electron transport layer can selectively extract and transport photogenerated electrons to the external circuit while blocking holes to prevent charge recombination. Since cuprous oxide typically exhibits p-type semiconductor characteristics, the electron transport layer in contact with it can be set as an n-type or highly conductive electron transport layer. The material of such an electron transport layer can be TiO2, ZnO, etc. The electron transport layer has a high electron mobility and a suitable bandgap arrangement, which can form an effective built-in electric field, accelerate the directional movement of electrons from the absorption layer to the first electrode, reduce the series resistance, and thus improve the fill factor and open-circuit voltage of the battery.

[0035] In the above embodiments, the hole transport layer can be located on the side of the absorption layer near the light-incident surface or on the side of the absorption layer near the back-light surface. When the electron transport layer is located on the side of the absorption layer near the light-incident surface, the hole transport layer is located on the side of the absorption layer near the back-light surface; conversely, when the electron transport layer is located on the side of the absorption layer near the back-light surface, the hole transport layer is located on the side of the absorption layer near the light-incident surface. The hole transport layer can selectively extract and transport photogenerated holes to the external circuit while blocking electrons. The cuprous oxide absorption layer, as a p-type semiconductor material, needs to efficiently collect the generated holes. The hole transport layer can be made of materials such as NiO, Spiro-OMeTAD, or CuSCN, and has a suitable valence band position that can match the valence band of the absorption layer, reducing the hole injection barrier. The hole transport layer ensures that holes can flow smoothly to the second electrode, reducing carrier recombination losses at the interface, thereby improving the overall quantum efficiency of the device.

[0036] In the above embodiments, the first and second electrodes are located on the outermost layer of the battery structure, respectively, and are used to collect photogenerated carriers output from the charge transport layer and guide them to an external load to form a current loop. The first electrode can contact the electron transport layer, and the second electrode can also contact the electron transport layer, responsible for collecting electrons; the second electrode can contact the hole transport layer, and the first electrode can also contact the hole transport layer, responsible for collecting holes. The first or second electrode on the light incident side can be a transparent conductive electrode (such as ITO, FTO), ensuring that the maximum amount of sunlight can penetrate into the absorption layer; while the first or second electrode on the back side is a metallic electrode (such as Ag, Al, Au, etc.), providing low-resistance ohmic contact and good reflection. When the first electrode is in contact with the electron transport layer, the second electrode is also in contact with the electron transport layer; conversely, when the second electrode is in contact with the electron transport layer, the first electrode is also in contact with the electron transport layer. The potential difference between the two electrodes drives the current to do work, realizing the final output of solar energy into electrical energy.

[0037] The copper oxide and cuprous oxide of this application can be stacked in the form of a thin film, with a compositional gradient layer between them; alternatively, copper oxide can be uniformly mixed in cuprous oxide. In the case of stacking in the form of a thin film, in some optional embodiments, such as... Figures 2 to 3 As shown, the cuprous oxide 11 structural layer has a first surface and a second surface arranged opposite to each other, and the copper oxide 12 structural layer is located on at least one of the first and second surfaces. This technical solution uses cuprous oxide 11 as the main structural layer, and copper oxide 12 is located on the surface of the cuprous oxide 11 structural layer as an independent structural layer. A copper oxide 12 thin film of controllable thickness can be generated or deposited in situ at the interface of the cuprous oxide 11 thin film through processes such as physical deposition or magnetron sputtering. This allows for a clear energy level arrangement between the two materials at the interface. The presence of surface copper oxide 12 can form a pn junction or pin heterojunction interface at the cuprous oxide 11 interface, which is beneficial for the rapid separation of photogenerated electrons and holes at the interface and reduces interface recombination losses. Copper oxide 12 has a narrower band gap and a higher absorption coefficient than cuprous oxide 11. Placing it on the surface, especially on the light incident side, can directly enhance the capture of red and near-infrared light, compensating for the absorption shortcomings of cuprous oxide 11, thereby increasing the short-circuit current density. The copper oxide 12 on the surface can also passivate the dangling bonds and defect states on the surface of the cuprous oxide 11, reduce the surface recombination rate, and thus improve the open-circuit voltage and fill factor. Specifically, the copper oxide 12 can cover only the first surface of the cuprous oxide 11, or only the second surface (not shown in the figure), or it can cover both sides of the first and second surfaces simultaneously. The first surface can be the light-incident surface and the second surface can be the back-light surface, or the first surface can be the light-incident surface and the second surface can be the back-light surface.

[0038] In the case where cuprous oxide and copper oxide are stacked in the form of thin films, in some optional embodiments, a transition layer is provided between the cuprous oxide structural layer and the copper oxide structural layer. The atomic ratio of copper to oxygen in the transition layer is between that in the cuprous oxide structural layer and that in the copper oxide structural layer. When cuprous oxide (Cu:O atomic ratio of approximately 2:1) and copper oxide (Cu:O atomic ratio of 1:1) form a stacked structure, there is a difference in lattice constant and chemical potential mismatch between the two, and the direct interface easily introduces high-density defect states and interface states. The transition layer introduced in this embodiment has a copper-oxygen atomic ratio between cuprous oxide and copper oxide (for example, it can be an intermediate or mixed valence oxide such as Cu4O3). In terms of physical structure, it acts as a buffer connecting two different lattice materials, or as a gradient transition. This gradient atomic ratio can form a smooth band transition, eliminate band abruptness or potential barriers at the interface, facilitate the smooth transport of photogenerated carriers between the two layers, reduce transport resistance, and improve the fill factor. Furthermore, this transition layer can be formed by controlling the gradual change of oxygen ratio during sputtering, element diffusion during annealing, or in-situ growth, so that the crystal structure, lattice parameters, and electronic state density can change smoothly from cuprous oxide to copper oxide. This can alleviate the lattice mismatch stress between cuprous oxide and copper oxide, reduce defects such as dislocations and vacancies at the interface, thereby reducing the density of recombination centers at the interface and improving minority carrier lifetime.

[0039] When cuprous oxide and copper oxide are stacked in the form of thin films, in some optional embodiments, the thickness of the copper oxide structural layer ranges from 10 nm to 200 nm, preferably from 10 nm to 50 nm. This thickness range refers to the dimension of the copper oxide thin film in the thickness direction of the solar cell. The aforementioned thickness range of the copper oxide structural layer can form a continuous and dense thin film, reducing pinhole defects and providing complete coverage of the cuprous oxide; it also avoids the absorption of excessive incident light, which could prevent the effective transport of photogenerated carriers to the junction region, or increase series resistance, thus negatively impacting cell performance. The aforementioned thickness range of the copper oxide structural layer can balance optical absorption enhancement and electrical transport efficiency. The aforementioned thickness can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, or 200 nm.

[0040] In some alternative embodiments, where copper oxide is uniformly mixed in cuprous oxide, such as... Figure 1As shown, the cuprous oxide structure includes copper oxide. In this embodiment, the absorber layer 10 is defined as copper oxide doped in the cuprous oxide matrix. In this case, the copper oxide does not exist as an independent macroscopic thin film layer, but is dispersed in the form of nanoparticles, nanocrystals, sheet structures, or atomic-level doping, within the lattice or at the grain boundaries of the cuprous oxide. The uniform dispersion of copper oxide in the cuprous oxide matrix can form a large number of nanoscale pn junctions or pin junctions. Due to the band shift between cuprous oxide and copper oxide, this dense heterojunction interface can increase the distribution area of ​​the built-in electric field, which is beneficial for the separation of photogenerated electron-hole pairs at the moment of generation, suppressing bulk recombination and improving carrier collection efficiency. Moreover, copper oxide has a narrower band gap than cuprous oxide, and the uniformly mixed copper oxide component can act as an additional light absorption center, effectively capturing long-wavelength photons that are difficult for cuprous oxide to absorb, and injecting the generated additional carriers into the cuprous oxide matrix, thereby significantly improving the short-circuit current density of the battery.

[0041] In the above-mentioned optional embodiments, this structure in which copper oxide is uniformly mixed in cuprous oxide can be achieved through reactive magnetron sputtering. For example, during the deposition of cuprous oxide thin films, by controlling parameters such as oxygen partial pressure, sputtering power, and substrate temperature, copper oxide phase can be naturally precipitated in the generated cuprous oxide grains, or a copper oxide shell can be formed in situ on the surface of the cuprous oxide grains, thereby forming a Cu2O / CuO nanoheterojunction network at the microscale. This bulk doping or nanocomposite structure allows for a high degree of integration of the two materials in three-dimensional space.

[0042] In the case where copper oxide is uniformly mixed in cuprous oxide, in some optional embodiments, the mass percentage of copper oxide in the cuprous oxide structural layer ranges from 0% to 10%. This range covers cases from pure cuprous oxide to composite materials rich in a small amount of copper oxide phase. Within this range, the introduction of a small amount of copper oxide is sufficient to form an effective nanoheterojunction in the cuprous oxide lattice, which can enhance the absorption capacity for light in the 600nm-800nm ​​wavelength band. This significantly increases the short-circuit current density without sacrificing the open-circuit voltage, thereby improving the overall conversion efficiency. Furthermore, within this mass percentage range, copper oxide can be dispersed in the form of nanoparticles, nanocrystals, or clusters within or at the grain boundaries of cuprous oxide, maintaining a single-phase or multi-phase microcrystalline structure dominated by cuprous oxide. This ratio can be precisely controlled by optimizing process parameters such as sputtering oxygen partial pressure. When the copper oxide content is below 0.1%, the enhancement effect on long-wavelength light absorption is not significant; when the content exceeds 10%, copper oxide exhibits high resistivity, and excessive copper oxide leads to increased film resistivity, easily forming too many recombination centers, and reducing carrier mobility and collection efficiency. The above range ensures that while enhancing long-wavelength light absorption, the high conductivity and carrier lifetime of the cuprous oxide substrate are not severely compromised.

[0043] In some alternative embodiments, the copper oxide morphology includes at least one of the following: nanoparticles, microparticles, flakes, discontinuous films, and continuous films. When cuprous oxide and copper oxide are stacked in the form of films, the copper oxide is deposited entirely on the surface of cuprous oxide to form a complete capping layer, which can be the continuous film described above; copper oxide is deposited on the surface of cuprous oxide in the form of island-like or granular aggregates to form a partial capping layer, which can be the discontinuous film described above; copper oxide crystals grow in a flake-like morphology at the interface to form a layered heterojunction, which can be the flake-like structure described above; copper oxide is attached to the interface in the form of particles or serves as an intermediate layer in a stacked structure, which can be the nanoparticles or microparticles described above. When copper oxide is uniformly mixed in cuprous oxide, the copper oxide is dispersed in the form of grains or clusters within or at the grain boundaries of the cuprous oxide matrix. This can be the aforementioned nanoparticles or microparticles. Copper oxide nanosheets may exist between or within cuprous oxide grains to form nanocomposite materials. This can be the aforementioned sheet-like structure. At the microscale, if the copper oxide content is high or the distribution is slightly uneven, local thin film-like regions or network structures may be formed within the matrix. These may exhibit thin film characteristics at the microscopic level. This can be the aforementioned discontinuous thin film or continuous thin film.

[0044] In the above-mentioned optional embodiments, nanoparticle or sheet-like morphologies can increase the contact interface area between cuprous oxide and copper oxide, forming a high-density nanoscale pn heterojunction, promoting the separation of photogenerated carriers and reducing bulk recombination. Discontinuous thin film morphologies, while introducing copper oxide characteristics, can retain some direct contact between cuprous oxide and the charge transport layer, which is beneficial for optimizing band alignment and reducing contact resistance. Continuous thin film morphologies can provide a more uniform interface barrier and more stable electrical contacts, suitable for constructing clear heterojunction interfaces. Micron-sized particles or specifically oriented sheet-like structures may generate light scattering effects, increasing the optical path length within the thin film, thereby improving the utilization rate of light in weak absorption bands. Furthermore, granular or discontinuous thin film structures can better alleviate interfacial stress caused by the difference in lattice constants between cuprous oxide and copper oxide, preventing film cracking or peeling, and improving the mechanical stability and lifetime of the device.

[0045] In the above-described optional embodiments, the aforementioned features define the specific physical morphology of copper oxide in or on a cuprous oxide substrate, encompassing a variety of structural forms ranging from nanoscale to microscale, and from discrete particles to continuous thin films. These morphologies can be precisely controlled by adjusting parameters such as oxygen partial pressure, deposition rate, substrate temperature, and annealing process during magnetron sputtering, thereby meeting different performance optimization requirements.

[0046] According to another embodiment of this application, a method for preparing a solar cell is provided, for preparing the aforementioned solar cell, such as... Figure 4 As shown, the preparation method includes:

[0047] Step S1, providing an absorption layer, the absorption layer comprising cuprous oxide and copper oxide;

[0048] Specifically, deposition processes such as magnetron sputtering and chemical vapor deposition can be used to prepare an absorption layer composed of cuprous oxide and copper oxide on a substrate. The absorption layer can be a nanocomposite structure in which copper oxide is uniformly mixed in a cuprous oxide matrix, or it can be a heterojunction structure formed by stacking copper oxide and cuprous oxide in the form of a thin film.

[0049] Step S2: An electron transport layer is formed on one side surface of the absorption layer;

[0050] Specifically, an electron transport material (such as TiO2, ZnO, SnO2, etc.) is deposited on at least one side of the prepared absorber layer to form an electron transport layer. The electron transport layer can form an n-type region in a pn junction or pin heterojunction, and its conduction band energy level matches the conduction band of the cuprous oxide / copper oxide composite absorber layer to facilitate the injection of photogenerated electrons from the absorber layer and their efficient transport to the external circuit, while blocking the reverse flow of holes.

[0051] Step S3: A hole transport layer is formed on the surface of the absorption layer facing away from the electron transport layer;

[0052] Specifically, on the opposite side of the absorption layer and the electron transport layer, a hole transport material (such as NiO, Spiro-OMeTAD, CuSCN, etc.) is deposited to form a hole transport layer. The hole transport layer can serve as a p-type or hole-selective layer, and its valence band level needs to be well aligned with the valence band of the absorption layer in order to efficiently extract photogenerated holes and transport them to the second electrode, while blocking electrons.

[0053] Step S4: Form a first electrode and a second electrode that are in contact with the electron transport layer and the hole transport layer, respectively.

[0054] Specifically, if the first electrode is located on the light incident side, the material can be a transparent conductive oxide thin film, such as ITO or FTO, which can be deposited on the electron transport layer to collect electrons and allow light to pass through; if the second electrode is located on the back side, the material can be a metal electrode, such as Ag, Al, Au, etc., which can be deposited on the hole transport layer to collect holes and provide good ohmic contact.

[0055] The solar cell prepared by the above-described method in this application contains a light-absorbing layer composed of both cuprous oxide and copper oxide, and a heterojunction structure consisting of an electron transport layer and a hole transport layer, which can improve the photoelectric conversion efficiency of the solar cell. Specifically, cuprous oxide, as a wide bandgap material, provides a good lattice basis; while the introduced copper oxide, as a narrow bandgap component, effectively compensates for the insufficient absorption of long-wavelength sunlight by cuprous oxide, thereby significantly enhancing the device's ability to utilize full-spectrum sunlight and increasing the short-circuit current density. Simultaneously, the microscopic heterojunction or interface barrier formed between copper oxide and cuprous oxide facilitates the separation and transport of photogenerated carriers, reducing recombination losses. Combined with the selective charge transport layers on both sides, it can further achieve efficient directional collection of electrons and holes to the corresponding electrodes, reducing series resistance. Ultimately, while maintaining the low-cost advantage, the cell achieves a higher open-circuit voltage and fill factor, resulting in a substantial improvement in overall photoelectric conversion efficiency, thus solving the problem of low photoelectric conversion efficiency in existing solar cells.

[0056] In some optional embodiments, the step S1 above, which forms the absorbent layer, includes:

[0057] A substrate is provided; the substrate is a temporary substrate provided for the preparation of the absorbent layer, and can be glass or other materials that allow the absorbent layer to be easily peeled off from its surface later.

[0058] A cuprous oxide layer is formed on a substrate using magnetron sputtering. During the fabrication of the absorber layer, argon and oxygen gases are introduced into the substrate surface. The target material is copper, and the atomic ratio of argon to oxygen is 5:1 to 10:1. Using a pure copper target, the ratio of argon (plasma gas) to oxygen (reactant gas) is adjusted, and deposition is performed in a copper-rich or near-stoichiometric reducing atmosphere. The reaction between the copper target and oxygen generates a crystal structure dominated by cuprous oxide. The atomic ratio of argon to oxygen can be 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1.

[0059] A transition layer is formed on a cuprous oxide structure using magnetron sputtering. During the fabrication of the absorber layer, the atomic ratio of argon to oxygen is 1:3 to 3:1. While maintaining uninterrupted sputtering, the oxygen ratio can be gradually increased to adjust it to 1:3 to 3:1 (moderate oxygen content). This forms a mixed-valence oxide (such as Cu4O3 or CuO-Cu2O solid solution) between cuprous oxide and copper oxide, serving as a buffer layer for lattice mismatch. The atomic ratio of argon to oxygen can be 1:3, 1:2.5, 1:1, 2:1, or 3:1.

[0060] A copper oxide structural layer is formed on the transition layer using magnetron sputtering. During the fabrication of the absorber layer using magnetron sputtering, the atomic ratio of argon to oxygen is 1:10 to 1:1. The oxygen ratio is further increased to adjust the argon to oxygen atomic ratio to 1:10 to 1:1 (high oxygen content). The atomic ratio of argon to oxygen can be 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, or 1:1.

[0061] According to another embodiment of this application, a stacked battery is proposed, comprising a bottom battery and a top battery, wherein the top battery is the aforementioned solar cell.

[0062] According to another embodiment of this application, a photovoltaic module is proposed, comprising a plurality of the aforementioned solar cells.

[0063] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0064] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A solar cell, characterized in that, include: The absorber layer comprises cuprous oxide and copper oxide; An electron transport layer is located on one side of the surface of the absorption layer; A hole transport layer is located on the surface of the absorption layer opposite to the electron transport layer. The first electrode and the second electrode are in contact with the electron transport layer and the hole transport layer, respectively.

2. The solar cell according to claim 1, characterized in that, The cuprous oxide structural layer has a first surface and a second surface disposed opposite to each other, and the copper oxide structural layer is located on at least one of the first surface and the second surface.

3. The solar cell according to claim 2, characterized in that, A transition layer is provided between the cuprous oxide structural layer and the copper oxide structural layer, wherein the atomic ratio of copper to oxygen in the transition layer is located between the atomic ratio of copper to oxygen in the cuprous oxide structural layer and the atomic ratio of copper to oxygen in the copper oxide structural layer.

4. The solar cell according to claim 2, characterized in that, The thickness of the copper oxide structural layer ranges from 10 nm to 200 nm.

5. The solar cell according to claim 1, characterized in that, The cuprous oxide structural layer includes the copper oxide.

6. The solar cell according to claim 5, characterized in that, The mass percentage of copper oxide in the cuprous oxide structural layer ranges from 0% to 10%.

7. The solar cell according to any one of claims 1 to 6, characterized in that, The copper oxide may be in at least one of the following forms: nanoparticles, microparticles, flakes, discontinuous films, and continuous films.

8. A method for preparing a solar cell, characterized in that, The method for preparing the solar cell according to any one of claims 1 to 7 comprises: An absorption layer is provided, the absorption layer comprising cuprous oxide and copper oxide; An electron transport layer is formed on one surface of the absorption layer; A hole transport layer is formed on the surface of the absorption layer opposite to the electron transport layer. A first electrode and a second electrode are formed to contact the electron transport layer and the hole transport layer, respectively.

9. The preparation method according to claim 8, characterized in that, The steps for forming the absorption layer include: Provide substrate; The cuprous oxide structural layer is formed on the substrate using a magnetron sputtering process. During the preparation of the absorption layer by the magnetron sputtering process, argon and oxygen are introduced into the surface of the substrate. The target material is copper, and the atomic ratio of the argon to the oxygen is 5:1 to 10:

1. A transition layer is formed on the cuprous oxide structural layer using a magnetron sputtering process. During the preparation of the absorption layer using the magnetron sputtering process, the atomic ratio of argon to oxygen is 1:3 to 3:

1. The copper oxide structural layer is formed on the transition layer using a magnetron sputtering process. During the preparation of the absorber layer using the magnetron sputtering process, the atomic ratio of argon to oxygen is 1:10 to 1:

1.

10. A stacked battery, characterized in that, It includes a bottom cell and a top cell, wherein the top cell is a solar cell according to any one of claims 1 to 7.

11. A photovoltaic module, characterized in that, The solar cells include any one of claims 1 to 7.